THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN THE DEVELOPMENT OF 21ST-CENTURY SKILLS AND CRITICAL THINKING SKILLS IN ISLAMIC RELIGIOUS EDUCATION - Fitriyanti Fitriyanti; Eprianto Eprianto; Sirozi Sirozi (LP2M IAI Al-Khairat Pamekasan, 2026)
Islamic Religious Education (PAI) in the 21st century is required not only to transfer religious knowledge but also to holistically develop students' critical thinking skills and 21st-century competencies. However, the reality in the field shows that PAI learning is still dominated by conventional methods that are less capable of optimally developing students' critical thinking abilities and 21st-century skills. This study aims to: (1) describe the planning and implementation of Project Based Learning (PjBL) in PAI; (2) analyze the development of 21st-century skills through PjBL in PAI; (3) examine the improvement of students' critical thinking skills through PjBL in PAI; and (4) analyze the relevance of PjBL to Islamic values and student character formation. This study employs a qualitative approach with a library research design, collecting and analyzing reputable national and international journal articles published between 2020 and 2025. The results show that the implementation of PjBL in PAI is proven effective in developing 21st-century skills including critical thinking, communication, collaboration, and creativity, while simultaneously internalizing Islamic values and forming students' character holistically and sustainably. PjBL is a highly relevant learning model and is recommended to be consistently applied in PAI learning at various educational levels.